Assessing the immediate impact of COVID‐19 on surgical oncology practice: Experience from an NCI‐designated Comprehensive Cancer Center in the Northeastern United States. Issue 1 (25th March 2021) - Gazivoda, Victor; Greenbaum, Alissa; Roshal, Joshua; Lee, Jenna; Reddy, Lekha; Rehman, Shahyan; Kangas‐Dick, Aaron; Gregory, Stephanie; Kowzun, Maria; Stephenson, Ruth; Laird, Amanda; Alexander, H. R.; et al.
Abstract: Background: The effects of the coronavirus disease 2019 (COVID‐19) pandemic on surgical oncology practice are not yet quantified. The aim of this study was to measure the immediate impact of COVID‐19 on surgical oncology practice volume. Methods: A retrospective study of patients treated at an NCI‐Comprehensive Cancer Center was performed. "Pre‐COVID" era was defined as January–February 2020 and "COVID" as March–April 2020. Primary outcomes were clinic visits and operative volume by surgical oncology subspecialty. Results: Abouyt 907 new patient visits, 3897 follow‐up visits, and 644 operations occurred during the study period. All subspecialties experienced significant decreases in new patient visits during COVID, though soft tissue oncology (Mel/Sarc), gynecologic oncology (Gyn/Onc), and endocrine were disproportionately affected. Telehealth visits increased to 11.4% of all visits by April. Mel/Sarc, Gyn/Onc, and Breast experienced significant operative volume decreases during COVID (25.8%, p = 0.012, 43.6% p < 0.001, and 41.9%, p < 0.001, respectively), while endocrine had no change and gastrointestinal oncology had a slight increase ( p = 0.823) in the number of cases performed. Conclusions: The effects of the COVID‐19 pandemic are wide‐ranging within surgical oncology subspecialties. The addition of telehealth is a viable avenue for cancer patient care and should be considered in surgical oncology practice.